Implementasi Peraturan Daerah Kabupaten Lampung Selatan Nomor 3 Tahun 2020 tentang Ketenteraman, Ketertiban Umum, dan Perlindungan Masyarakat - Edi Widarto (Amsir Law Journal, 2022)
The type of research used by the author is a normative-empirical type of research. This article was published to find out and analyze the implementation of the South Lampung Regency Regional Regulation Number 3 of 2020 concerning Peace, Order, and Community Protection. Research shows that the inhibiting factors for the implementation of the South Lampung Regency Regional Regulation Number 3 of 2020 concerning Public Order and Community Protection include human resources, facilities and infrastructure issues, as well as budget issues. Second, the factor of obedience and public awareness in complying with local regulations. In addition, the South Lampung Regency Regional Regulation Number 3 of 2020 concerning Public Order and Community Protection has been implemented, but not optimally—especially regarding the guidance, control, and supervision carried out by the Regional Regulation Enforcement Agency or the State Civil Apparatus or ASN.